Pengaruh Kualitas Sistem Informasi dan Kondisi Nyata Penggunaan Sistem Terhadap Kepuasan Pengguna Sistem Informasi Akuntansi Pada PT. Bank Sulutgo Kota Gorontalo - Laksmi Dewi Sari; Sahmin Noholo; Usman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the effect of information system quality and actual system usage on user satisfaction of the accounting information system at Pt. Bank Sulutgo, Gorontalo City. The type of method used in this research is a quantitative method with data collection techniques using questionnaire surveys and observation. The number of respondents in this study was 60 respondents consisting of AKL, General, Credit, Operations, Funds, Perben at Pt. Bank Sulutgo, Gorontalo City. The tool used in this research uses multiple linear regression analysis. The research results show that 1. The quality of the information system is positive and significant on user satisfaction of the accounting information system at Pt. Bank Sulutgo, Gorontalo City. 2. Actually system usage has a positive and significant effect on user satisfaction of the accounting information system at Pt. Bank Sulutgo, Gorontalo City. 3. Simultaneously, the quality of the information system and actual system usage have a positive effect on user satisfaction of the accounting information system at Pt. Bank Sulutgo Gorontalo City with a determinant value of 73.9% while the remaining 26.1% is explained by other variables not examined in this research.